China’s role in the EU’s discursive ‘spatialization’ of Africa: A critical geopolitical approach - Ribeiro, I. M.; Pereira, R. (The Palgrave handbook on China-Europe-Africa relations, 2024)
Stemming from the structural implications that global normative geopolitical shifts represent for our societies, literature on the intersection between History, Geopolitics, and Discourse grew under Critical Geopolitics (CrG). This hybrid sub-disciplinary field is gaining interest for its approach to deconstructing and critiquing the ‘spatialization’ of international politics and of the normative character of competing geopolitical imaginations (Ó’Tuathail & Agnew, 1992). Recent case studies include China (Gonzalez-Vicente, 2021), Asia-Pacific (Zeng & Zhang, 2021), Russia (Omelicheva, 2016), even outer space (Klinger, 2021). And while a lot has been written about EU-China relations (Geeraerts, 2013; Levy & Révész, 2021), EU-Africa relations (Haastrup, 2013; Haastrup et al., 2021), and China-Africa relations (Xing & Farah, 2016; Kalu, 2021), there is a topic warranting further research: how the EU has reacted to China’s presence and influence in one of its (if not the) most important foreign policy regions? Against this backdrop, the proposed research aims to address this knowledge gap by studying how the EU’s discursive ‘spatialization’ of Africa as its area of responsibility in the fields of security and development factors in China’s growing interests and presence therein, which are substantially normatively different than those of the EU. In order to do so, a CrG-based empirical study is proposed, based on the triangulation of critical discourse analysis and document analysis of corpora, as well as scientific literature. The chapter is expected to contribute to the deepening of the knowledge of an area in EU-China relations that may appear marginal, but is, in fact, crucial for the projection of each actor’s foreign policy interests and identity. The chapter also contributes to furthering the debate on CrG, and its primary focus on the EU’s perspective leaves room for future research focusing on China’s viewpoint.